Validation of Alternative Methods of Detection of Salmonella Spp. in Experimentally Contaminated Poultry Environmental Samples - Coelho,LR (2021)
ABSTRACT The analysis of Salmonella in the feces and the birds’ environment is a way of monitoring the colonization in the flocks and verifying the need for the introduction of stricter controls, in such a way that the results of the tests should be known before being sent for slaughter. The polymerase chain reaction (PCR), as well as other rapid methods represent alternatives increasingly used to detect enteric pathogens, but they need proof of effectiveness for their wide use. The aim of this study was to evaluate the equivalence between the results obtained by the methods: real-time PCR (BAX® System), Modified Rappaport-Vassiliadis Semi-solid Medium (MSRV) (ISO 6579) and the traditional method of official reference in Brazil for research of S. Typhimurium and S. Enteritidis in poultry samples. Two hundred and fifty-two samples of disposable shoe covers (DSC) and 252 samples of feces were infected with an average of 2 to 3 log CFU/g of each serovar, and the same samples without fortification were evaluated by the three methods. Five hundred and four diagnoses were obtained with satisfactory results in terms of repeatability (greater than 80%), reproducibility (mean 83,1%), sensitivity (81% to 100%), specificity (95% to 100%), and accuracy (90% to 100%). The compliance test verified that there was not a significant difference between the alternative and the official methods, allowing us to state that the methodologies have had equivalent performances.